The Malawi National Tuberculosis Programme: an equity analysis - Chimzizi Rhehab; Banda Hastings; Bello George; Simwaka Bertha; Squire Bertel SB; Theobald Sally J (BMC, 2007)
Abstract Background Until 2005, the Malawi National Tuberculosis Control Programme had been implemented as a vertical programme. Working within the Sector Wide Approach (SWAp) provides a new environment and new opportunities for monitoring the equity performance of the programme. This paper synthesizes what is known on equity and TB in Malawi and highlights areas for further action and advocacy. Methods A synthesis of a wide range of published and unpublished reports and studies using a variety of methodological approaches was undertaken and complemented by additional analysis of routine data on access to TB services. The analysis and recommendations were developed, through consultation with key stakeholders in Malawi and a review of the international literature. Results The lack of a prevalence survey severely limits the epidemiological knowledge base on TB and vulnerability. TB cases have increased rapidly from 5,334 in 1985 to 28,000 in 2006. This increase has been attributed to HIV/AIDS; 77% of TB patients are HIV positive. The age/gender breakdown of TB notification cases mirrors the HIV epidemic with higher rates amongst younger women and older men. The WHO estimates that only 48% of TB cases are detected in Malawi. The complexity of TB diagnosis requires repeated visits, long queues, and delays in sending results. This reduces poor women and men's ability to access and adhere to services. The costs of seeking TB care are high for poor women and men - up to 240% of monthly income as compared to 126% of monthly income for the non-poor. The TB Control Programme has attempted to increase access to TB services for vulnerable groups through community outreach activities, decentralising DOT and linking with HIV services. Conclusion The Programme of Work which is being delivered through the SWAp is a good opportunity to enhance equity and pro-poor health services. The major challenge is to increase case detection, especially amongst the poor, where we assume most 'missing cases' are to be found. In addition, the Programme needs a prevalence survey which will enable thorough equity monitoring and the development of responsive interventions to promote service access amongst 'missing' women, men, boys and girls.